The R&D-patent relationship: An industry perspective - Jérôme Danguy; Gaétan de Rassenfosse; Bruno van Pottelsberghe de la Potterie (EIB Papers, 2009)
This paper re-visits the empirical failure to establish a clear link between R&D efforts and patent counts at the industry level. It is claimed that the 'propensity-to-patent' concept should be split into an 'appropriability propensity' and a 'strategic propensity'. The empirical contribution is based on a unique panel dataset composed of 18 industries in 19 countries over 19 years. The results confirm that the R&D-patent relationship is affected by research productivity, appropriability propensity and strategicpropensity factors. The observed increase in the propensity to file patents is much stronger for supranational (that is, triadic or regional) patents than for national priority filings, suggesting that the current patent hype is essentially the result of a globalization phenomenon.
Keywords: 330; Industrielle Forschung; Innovation; Patent; EU-Staaten; Japan; USA